2002
DOI: 10.1152/ajpregu.00123.2002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological significance of α2-adrenergic receptor subtype diversity: one receptor is not enough

Abstract: Alpha(2)-adrenergic receptors mediate part of the diverse biological effects of the endogenous catecholamines epinephrine and norepinephrine. Three distinct subtypes of alpha(2)-adrenergic receptors, alpha(2A), alpha(2B), alpha(2C), have been identified from multiple species. Because of the lack of sufficiently subtype-selective ligands, the specific biological functions of these receptor subtypes were largely unknown until recently. Gene-targeted mice carrying deletions in the genes encoding for individual al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
214
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(236 citation statements)
references
References 85 publications
(118 reference statements)
13
214
0
5
Order By: Relevance
“…Recent studies on gene-targeted mice have confirmed that non-a 2A -AR subtypes also are involved in the autoreceptor function (for a review, see Philipp et al, 2002). This was also supported by the current study showing that, although statistically significant only in the cortex, D-amph supplementation with Ati tended to cause an additional NE decrease and an MHPG increase in a 2A -KO mice, too.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies on gene-targeted mice have confirmed that non-a 2A -AR subtypes also are involved in the autoreceptor function (for a review, see Philipp et al, 2002). This was also supported by the current study showing that, although statistically significant only in the cortex, D-amph supplementation with Ati tended to cause an additional NE decrease and an MHPG increase in a 2A -KO mice, too.…”
Section: Discussionsupporting
confidence: 88%
“…The a 2C -AR subtype, as well as the a 2A -AR, participated in a negative feed-back loop regulating norepinephrine release (Brede et al 2003;Philipp et al 2002). Studies in gene-targeted mice have demonstrated that disruption of a 2C -AR causes increased circulating catecholamine levels, which will consequently lead to enhanced cardiac b-AR signaling, development of dilated cardiomyopathy, and increased mortality resulting from heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…Among three subtypes of a 1 -ARs, the a 1A -AR is the predominant subtype in both the heart and vasculature and is a major contributor involved in the sympathetic regulation of blood pressure and peripheral vascular resistance (Guimaraes and Moura 2001;Tanoue et al 2002). Meanwhile, a 2 -ARs are important regulators of sympathetic tone, neurotransmitter release, blood pressure, and lipolysis in fat tissue (Lafontan and Berlan 1995;Philipp et al 2002). They are widely expressed in the human central and peripheral nervous systems, and a 2A -and a 2C -AR are presynaptic receptor subtypes that contribute to feedback control of norepinephrine release from sympathetic nerves (Brede et al , 2003Philipp et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, only agonist activation of the α 2A but not the α 2B AR subtype can cause this effect in a detectable fashion, despite the fact that both subtypes interact with spinophilin [89]. This subtype-selective enrichment of spinophilin may represent a mechanism contributing to subtype signaling diversity between the α 2A and the α 2B AR, which may serve as a base for different physiological functions elicited by these two subtypes [90].…”
Section: Other Potential Functions Of Spinophilinmentioning
confidence: 97%